PFKM-Mediated Glycolysis: A Pathway for ASIC1 to Enhance Cell Survival in the Acidic Microenvironment of Liver Cancer - Xiaomin Wu; Boshi Wang; Yingjian Hou; Yipeng Fang; Yuan Jiang; Yuelei Song; Youyi Liu; Cheng Jin (Biomolecules)
The acidic tumor microenvironment plays a critical role in promoting liver cancer cell survival by enhancing glycolysis and adaptive mechanisms. Acid-sensing ion channel 1 (ASIC1) is a key regulator of pH sensing, but its role in liver cancer progression and underlying mechanisms remain unclear. In this study, we examined ASIC1 expression in clinical liver tumor tissues using immunohistochemistry and immunofluorescence, correlating it with tumor stages. HepG2 and Li-7 cells were cultured in tumor supernatant and acidic conditions to mimic the tumor microenvironment. Western blotting assessed the expression of ASIC1 and glycolysis-related enzymes, with siRNA transfections used to investigate ASIC1 and phosphofructokinase muscle-type (PFKM) in liver cancer cell survival. Our results showed that ASIC1 expression was significantly elevated in liver tumor tissues and correlated with tumor progression. Acidic conditions increased ASIC1 expression in both cell lines, enhancing cell survival, while knockdown of ASIC1 reduced viability and increased apoptosis, particularly under acidic conditions. Moreover, PFKM silencing reversed the survival advantage conferred by ASIC1, confirming PFKM as a critical downstream effector. Additionally, lactate dehydrogenase (LDH) and phosphofructokinase (PFK) activity assays showed no significant changes, suggesting other regulatory mechanisms may also be involved. These findings suggest that the ASIC1/PFKM pathway promotes liver cancer cell survival in acidic environments, representing a potential therapeutic target for disrupting tumor adaptation in liver malignancies.